CFD simulation of effect of anode configuration on gas-liquid flow and alumina transport process in an aluminum reduction cell - Zhan, Shui-qing; Li, Mao; Zhou, Jie-min; Yang, Jian-hong; Zhou, Yi-wen (Journal of Central South University, 2015)
Numerical simulations of gas-liquid two-phase flow and alumina transport process in an aluminum reduction cell were conducted to investigate the effects of anode configurations on the bath flow, gas volume fraction and alumina content distributions. An Euler-Euler two-fluid model was employed coupled with a species transport equation for alumina content. Three different anode configurations such as anode without a slot, anode with a longitudinal slot and anode with a transversal slot were studied in the simulation. The simulation results clearly show that the slots can reduce the bath velocity and promote the releasing of the anode gas, but can not contribute to the uniformity of the alumina content. Comparisons of the effects between the longitudinal and transversal slots indicate that the longitudinal slot is better in terms of gas-liquid flow but is disadvantageous for alumina mixing and transport process due to a decrease of anode gas under the anode bottom surface. It is demonstrated from the simulations that the mixing and transfer characteristics of alumina are controlled to great extent by the anode gas forces while the electromagnetic forces (EMFs) play the second role.